FUNDAMENTALS OF SCIENTIFIC RESEARCH IN CIVIL AVIATION: FUNDAMENTOS DA PESQUISA CIENTÍFICA EM AVIAÇÃO CIVIL - Guimarães , Felipe Gontijo; Rodrigues , Rodrigo Luiz de Souza (Revista Brasileira de Aviação Civil & Ciências Aeronáuticas, 2025)
This article explores the fundamental steps of scientific research and their application to the civil aviation sector, emphasizing key methodologies: qualitative, quantitative, and mixed. Based on a theoretical review and an analysis of the characteristics of these approaches, it demonstrates how each method can be employed to investigate technical, operational, and human-related issues. Qualitative research is highlighted for its ability to delve into complex phenomena and interpret organizational and cultural contexts, while the quantitative approach excels in analyzing numerical data and validating large-scale hypotheses. Mixed methodologies combine the strengths of both qualitative and quantitative approaches, proving particularly effective in interdisciplinary studies involving technical and human factors. The article also discusses the importance of triangulation to enhance the validity of analyses and the strategic use of tools such as questionnaires and interviews in future investigations. It concludes that the careful selection and integration of different methodologies can significantly enrich research in the aeronautical sector, aligning academic rigor with practical demands. Keywords: Scientific Methodology; Civil Aviation; Qualitative Research; Quantitative Research; Mixed Methodology. RESUMO O presente artigo explora as etapas fundamentais da pesquisa científica e sua aplicação no setor de aviação civil, destacando alguns tipos de metodologias: qualitativa, quantitativa e mista. Com base em uma revisão teórica e na análise das características dessas abordagens, demonstra-se como cada método pode ser utilizado para investigar problemas técnicos, operacionais e humanos. A pesquisa qualitativa é reconhecida por sua capacidade de explorar fenômenos complexos e interpretar contextos organizacionais e culturais, enquanto a abordagem quantitativa se destaca na análise de dados numéricos e na validação de hipóteses em larga escala. A metodologia mista combina os pontos fortes das abordagens qualitativa e quantitativa, sendo especialmente aplicada em estudos interdisciplinares e que envolvem fatores técnicos e humanos. O artigo discute ainda a importância da triangulação, da sistematicidade, da replicabilidade e da objetividade para ampliar a validade das análises e a possibilidade de uso estratégico de instrumentos como questionários e entrevistas em investigações futuras. Palavras-chave: Metodologia Científica; Aviação Civil; Pesquisa Qualitativa; Pesquisa Quantitativa; Metodologia Mista.